Telenursing - Kumar, Sajeesh. (Health informatics, 2011)
Developments in telenursing are occurring at a great pace. In a very short time and driven by technical developments, the field of telenursing has become too extensive to be covered by only a small number of experts. As a consequence, there is a need for a broad overview of the field to enable the concepts to be understood by a wider population. Telenursing is presented in such a way that it should make it accessible to anyone, independent of their knowledge of technology and has been written with contributions from a host of renowned international authorities in telenursing. Books on theoretical and technical aspects inevitably use technical jargon, and this book is no exception, but it is kept to a minimum in an effort to maximize clarity. Moreover the book has been organised systematically, thus ensuring that the content is concise and easy to read. Every chapter provides a comprehensive list of citations and references for further reading. Figure drawings and clinical photographs throughout the book illustrate and illuminate the text, providing readers with high-quality visual reference material. It is therefore appropriate for all professionals, including nurses, physicians, allied health professionals and computer scientists to help them understand the changes going on and how best to make use of them in practice. Introduction to telenursing -- Teaching telenursing with the Charles Darwin University Virtual Hospital -- Telenursing: current scenario and challenges for Brazilian nursing -- Telehealth nursing in Canada: opportunities for nurses to shape the future -- Telenursing in an emerging economy: an overview -- Telenursing in chronic conditions -- Telenursing in Korea -- Telenursing in a developing country: the Philippine experience -- New trends in diagnosis support and role of nurses based on RIGHT-like systems -- Telenursing in chronic respiratory diseases -- Telenursing in Africa -- Telenursing in Sweden -- Telenursing in the UK: a brief profile of National Health Service Direct -- Supporting the UK patient with a long-term condition: policy, strategy, education, and telehealth -- Telenursing in New Zealand -- Telenursing in the United States -- Telenursing: an audit.